SIMBOL DAN MAKNA TARI JEPIN PESAWAT TERBANG DI KOTA PONTIANAK KALIMANTAN BARAT - Ciprilia Dian Trismidita; Imma Fretisari; Asfar Muniir (Universitas Tanjungpura, 2020)
Abstract This research was motivated to learn about symbols and meanings of dance jepin Aircraft. The purpose of this study was. To describe the symbol and meaning of dance jepin Pesawat Terbang In Kota Pontianak Kalimantan Barat. Descriptions of the contribution of research results in junior high school level learning unit. The method used was descriptive method with qualitative terms and use etnokoreologi approach, with the data source Juhermi Tahir Anwar Djafar who knows about symbols and meanings of dance jepin Pesawat Terbang. The data that was colleceted using observation, interview and documentation. validity of data in the form of triangulation sumber. Tari jepin Pesawat Terbang there is some movement, which has meaning and symbols. Step bekayuh bekayuh presents symbols and meanings that the dancers began to enter on the left and right of the stage. Motion stunted step Delivers fast symbols and motion stunted step Delivers fast symbol. Motion unusual step of walking and presenting symbols have meaning that life must have humility in the mix and behave. The sliding motion sewing needle presents symbols and meaning of human life should be lived with a view not to be affected straight bad things. Motion hanging step presents symbols and meanings that hang in life must be dependent to the one God and fellow human beings. Keywords: Dancing jepin Pesawat Terbang, meanings, symbols